1998
DOI: 10.1017/s0048577298970998
|View full text |Cite
|
Sign up to set email alerts
|

Extinction in fear conditioning: Effects on startle modulation and evaluative self-reports

Abstract: A basic feature of human evaluative conditioning is that the reported acquired valence of a previously neutral conditioned stimulus (CS) that has been paired with a valenced unconditioned stimulus (US), is resistant to extinction. The present study investigated whether startle modulation, sometimes presented as an index of acquired valence, reflected this basic feature. In a differential fear conditioning paradigm (n = 38) with an electrocutaneous stimulus as the US, a strong extinction manipulation was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 14 publications
7
25
0
3
Order By: Relevance
“…In fact, in none of the three studies did the CS_Neg (equivalent of CSþ in other differential conditioning designs) reach levels of the CS_Neu (~CS-) by the end of the extinction phase, even in the more extended extinction procedures in Studies 2 and 3. This is consistent with previous research on the persistence of EC (e.g., Vansteenwegen et al, 1998;Vansteenwegen et al, 2006) and makes it an important target for extinction research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, in none of the three studies did the CS_Neg (equivalent of CSþ in other differential conditioning designs) reach levels of the CS_Neu (~CS-) by the end of the extinction phase, even in the more extended extinction procedures in Studies 2 and 3. This is consistent with previous research on the persistence of EC (e.g., Vansteenwegen et al, 1998;Vansteenwegen et al, 2006) and makes it an important target for extinction research.…”
Section: Discussionsupporting
confidence: 92%
“…EC has a number of characteristics that make it different from expectancy learning. EC is more resistant to extinction than expectancy learning (Blechert, Michael, Williams, Purkis, & Wilhelm, 2008;Hermans, Vansteenwegen, Crombez, Baeyens, & Eelen, 2002;Vansteenwegen, Crombez, Baeyens, & Eelen, 1998;Vansteenwegen, Francken, Vervliet, De Clercq, & Eelen, 2006). EC is also associated with reinstatement (Dirikx, Hermans, Vansteenwegen, Baeyens, & Eelen, 2004;Hermans et al, 2005;Zbozinek, Hermans, Prenoveau, Liao, & Craske, 2014), a laboratory analogue of the return of fear after an initially successful treatment (Rachman, 1989) which makes EC particularly relevant for the long term outcome of exposure therapies.…”
Section: Integrating Cognitive Emotion Regulation With Pavlovian Condmentioning
confidence: 99%
“…On the contrary, the reinstatement effect in the behavioral measure (FPS) was not persistent but was extinguished quickly, because the analysis of both re-extinction phases on Day 3 showed no significant difference between CXT+ and CXT-anymore. This is in line with a study which showed extinction in SCR and startle responses but absent extinction in valence ratings (Vansteenwegen et al, 1998). Maybe, a stronger and more persistent reinstatement effect in FPS could have been observed, if the state anxiety before the reinstatement procedure became even higher.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this body of work, the human startle reflex is enhanced in the context of aversive stimuli and situations: startle magnitude is larger in the presence of conditioned stimuli (Grillon & Davis 1997) and in response to threat of shock (Grillon et al 1991); moreover, startle magnitude tracks the association between conditioned and unconditioned stimuli across acquisition and extinction periods of fear conditioning (Vansteenwegen et al 1998;Walker et al 2002).…”
supporting
confidence: 64%